The Effect of Giving Incentives on Employee Performance at PT. Gemilang Perkasa in Jakarta - Hanif, Hernawan; Suratminingsih, Suratminingsih; Haryadi, Rofiq Noorman (Management Science Doctoral Program, Pasundan University, Bandung, Indonesia, 2023)
This study aims to determine the effect of providing incentives on employee performance at PT Gemilang Perkasa in Jakarta. The method used is explanatory research with a sample of 82 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this research variable giving incentives obtained an average score of 3.81 with good criteria. The employee performance variable obtained an average score of 3.90 with good criteria. Providing incentives has a significant effect on employee performance with the regression equation Y = 14.343 + 0.647X, and a correlation value of 0.760 or having a strong relationship with a contribution of 57.8% and the hypothesis test obtained sig. 0.000 < 0.05.